Process work in urgency and emergency in interface with the death - Dell´Acqua, Magda Cristina Queiroz [UNESP] (2013)
This qualitative study aimed to understand the experience of nursing professionals in the working process with adult patients and their families who experience the death event in emergency rooms. One analyzed narratives of 12 professionals, from an emergency room in a university hospital of high complexity, in Botucatu, São Paulo. Data collection occurred from December 2008 to April 2009, through semi-structured interviews. Using content analysis, the central theme emerged: The organization of work in urgency and emergency rooms, with four subcategories: Death as a working routine, Teamwork, Motivation at Work, and Death at a teaching hospital. One concluded that the possibilities of personal and professional growth, the need, and the desire to intervene were identified as motivators for working in emergency rooms, even when it is permeated by death.